Basic Methods Of Reconciling Issues Using A Geometric Method - Gulhayo Bahodirovna Quzmanova (Euro Asian Journal Publishing, 2024)
Word problems are one of the main concepts of the school mathematics course. In this article, solving text problems about concentration and mixing using the geometric method allows students to develop thinking, attention and observation, independently performing small studies, as well as their skills.
Keywords: school; mathematics; geometric